Zeros of Jacobi-Sobolev orthogonal polynomials following non-coherent pair of measures - de Andrade, Eliana X.L. [UNESP]; Bracciali, Cleonice Fátima [UNESP]; de Mello, Mirela V. [UNESP]; Pérez, Teresa E. (Brazilian Society for Computational and Applied Mathematics (SBMAC), 2010)
Zeros of orthogonal polynomials associated with two different Sobolev inner products involving the Jacobi measure are studied. In particular, each of these Sobolev inner products involves a pair of closely related Jacobi measures. The measures of the inner products considered are beyond the concept of coherent pairs of measures. Existence, real character, location and interlacing properties for the zeros of these Jacobi-Sobolev orthogonal polynomials are deduced. © 2010 SBMAC.
Keywords: Jacobi orthogonal polynomials; Sobolev orthogonal polynomials; Zeros of orthogonal polynomials